الموظف العام بين المتابعة القضائية والعقوبة التأديبية - غانم, حسين (University of Eloued جامعة الوادي, 2017)
تناولت هذه المذكرة الموظف العام بين المتابعة القضائية والعقوبة التأديبية حيث تتمحور إشكالية هذه الدراسة حول الإطار القانوني الذي يحكم العلاقة مابين المتابعة التأديبية عن المتابعة القضائية للموظف العام وفي إطار النصوص التنظيمية الخاصة به وكذا إبراز مدى استقلالية المتابعة القضائية عن المتابعة التأديبية ومدى تأثر كل منهما على الأخرى. حيث تم استخدام المنهج التحليلي وذلك من خلال إجراء دراسة تحليلية للقانون الوظيفة العمومية الساري المفعول لاسيما في شقه التأديبي وكذا تم التطرق إلى النصوص القانونية ذات الصلة. وتم تقسيم هذه الدراسة إلى فصلين، حيث بين الباحث في الفصل الأول منها مدى استقلالية المتابعة القضائية عن المتابعة التأديبية للموظف العام من خلال مدى استقلال الدعويين التأديبية والجزائية من حيث الجهة المختصة بتوجيه الاتهام والأساس القانوني لها، وعن مدى تأثير التحقيق الجزائي على التحقيق الإداري من حيث ثبوت الخطأ والسلطة المختصة في ممارسة الإجراءات التأديبية، والضمانات المقررة للموظف في مثوله أمام اللجنة المتساوية الأعضاء وفي الفصل الثاني من هذه الدراسة تعرض الباحث إلى حجية الحكم الجزائي وأثره على التأديب الوظيفي من خلال تسليط الضوء على الطبيعة القانونية للحكم الجنائي الصادر بالإدانة أو بالبراءة من المحكمة المختصة في مواجهة سلطات التأديب المختصة، وكذا إجراء أوجه الشبه والاختلاف بين الجريمة التأديبية والجريمة الجنائية. وفي الأخير تم التوصل إلى بعض النتائج من أهمها:أن الأمر 06-03 لا سيما في شقه التأديبي لم يأتي بالجديد بحيث جاءت نصوصه مشابهة لما كان موجود في السابق، كما أن نصوصه لم تفسر شيء عن الحجية التي يتمتع بها الحكم الجزائي أمام سلطات التأديب.This brief deals with the facts committed by an official can lead to both disciplinary proceedings and criminal prosecution. Both repressions have different objectives, protection of the interests of the service in one case, protection of society without And they are quite independent. The issue of this study focuses on the legal framework that governs the relationship between the disciplinary follow-up on the judicial follow-up of an official and its regulations, Using the analytical study of the law of the public service in force, especially on its disciplinary side, as well as the legal texts relating thereto. This study was divided into two chapters. In the first chapter, the researcher explained the extent of the independence of the judicial follow-up of the disciplinary follow-up of an official, as well as the extent of the independence of the disciplinary and penal procedures with regard to the responsible authority Indictment and its legal basis. The influence of the criminal investigation on the administrative investigation and the fault committed and the competent authority in the exercise of disciplinary proceedings and the guarantees provided for the official before the Joint Committee. In the second chapter of this study the researcher is exposed to the authority of the criminal judgment and its impact on the discipline by clarifying the legal nature of the criminal judgment pronounced by the competent court against the competent disciplinary authorities, as well as similarities And differences between disciplinary and criminal crimes. Finally, some results have been achieved. The most important of these results is that Law 06-03, especially in its disciplinary aspect, has not presented new texts, similar to those that existed in the past, and its texts have not explained the legitimacy Which the penalties enjoy before the disciplinary authorities.
مدكرة ماستر